CROWN SEPARATION WITH USE ELECTROFULGURATION AT BOTTOM OF DENTAL CAVITY - S.V. Irkha (Український стоматологічний альманах)
Actuality of theme. In recent years the development of endodontics and the use of new technologies enhanced the efficiency of root canal treatment. But this does not completely solve the problem of the teeth roots perforation in the area of furcation.